Bees Casting Shadows on a Cloudy Day: An Afterword - John Durham Peters (Media Theory)
In this afterword, the author of Speaking into the Air engages in correspondence with some of its critics.  Rather than dialogues with the dead these are letters to the living.  As acts of writing in hopes of connection, they are enactments and enhancements of the book’s arguments.